2007
DOI: 10.1007/s00417-007-0707-1
|View full text |Cite
|
Sign up to set email alerts
|

Topical antisense-oligonucleotides targeting IFN-gamma mRNA improve incidence and severity of herpetic stromal keratitis by cytokine specific and sequence unspecific effects

Abstract: Topical treatment with IFN-gamma-ASON induced a long-term improvement of the course and the incidence of HSK in the murine model. IFN-gamma seems to be involved in a proinflammatory manner during the pathogenesis of HSK, while the antiviral defense against HSV was not affected by this topical cytokine inhibition. Unspecific CON induced a transient and cytokine independent improvement of HSK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Viral loads of infected eyes were measured on day 5 post infection with a standard plaque assay (N = 6 in each group) [ 30 ]. The inflammatory cells in the corneas were counted as previously described [ 31 ]. Total cell numbers in spleens and lymph nodes were counted after the homogenization of the organs with a 70 µm cell strainer (BD Biosciences, Franklin Lakes, NJ, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Viral loads of infected eyes were measured on day 5 post infection with a standard plaque assay (N = 6 in each group) [ 30 ]. The inflammatory cells in the corneas were counted as previously described [ 31 ]. Total cell numbers in spleens and lymph nodes were counted after the homogenization of the organs with a 70 µm cell strainer (BD Biosciences, Franklin Lakes, NJ, USA).…”
Section: Methodsmentioning
confidence: 99%
“…IFN-γ is generally detected on 3 dpi in the inflamed sites of corneal stroma and lasts until 12 dpi (51). The treatment of HSK with antisense oligonucleotides targeting IFN-γ mRNA (IFN-γ-ASON) in vitro and in vivo obviously improves the incidence of HSK (52). However, another study demonstrated that IFN-γ has a dual role in the HSV-1-induced immune response.…”
Section: Regulation Of Anti-inflammatory Cytokines In Hskmentioning
confidence: 99%
“…10 μL of 0.5% CSA/mPEGhexPLA micelle formulation contained 0.05 mg of CsA; the total administered drug dosage per mice averaged 0.25 mg of CsA/day (15.6 mg of CsA/kg/day). Because of the reconstitution of drug-loaded micelles in phosphate buffered solution and according to previous studies of topical regimen, ,,, PBS was used as control treatment in this study.…”
Section: Methodsmentioning
confidence: 99%